FAKTOR-FAKTOR YANG MEMPENGARUHI EARNINGS PERSISTENCE PADA PERUSAHAAN BASIC MATERIAL - Ivone, Margiota Fiona; Bangun, Nurnainun; Kurniawati, Herni (Jurnal Paradigma Akuntansi, 2025)
The purpose of this study was to find out whether factors such as cash flow volatility, company size, and accrual reliability affect earnings persistence with the research subject being the basic ingredients of sector companies listed on the Indonesia Stock Exchange (IDX) during 2018-2020. The sampling technique used was purposive sampling so that the number of sample data obtained was 108 (after outliers). Data processing uses multiple linear regression analysis techniques with the data processing tool used, namely SPSS 25.0. The results showed that the cash flow volatility variable has a significant effect on earnings persistence, while the firm size and accrual reliability variables have no significant effect on earnings persistence. The implication of this research is that the volatility of cash flows indicates a good use of cash resources and maximum effort in maintaining profit stability due to fluctuations in cash flows in order to maintain stakeholder confidence.